Persepsi Guru terhadap Implementasi Kurikulum Merdeka Sebuah Pendekatan Kualitatif di Sekolah Dasar Inpres Sahapikya Distrik Venaha Kabupaten Mappi Provinsi Papua Selatan - Udin Abubekar; Sedarmayanti Sedarmayanti; Dety Mulyanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Independent Curriculum is an initiative launched by the Ministry of Education and Culture of the Republic of Indonesia to provide freedom for teachers and students in the learning process. This study aims to explore the perception of teachers at Inpres Sahapikya Elementary School towards the implementation of the Independent Curriculum. Through a qualitative approach, data was collected through in-depth interviews with 6 teachers who taught at the school. The results showed that although teachers had a positive view of the flexibility and innovation offered by the Independent Curriculum, there were a number of challenges faced, including a lack of training and support from management. This research provides valuable insights into how teachers' perceptions can affect the success of curriculum implementation in the field.